Moralno razumevanje prava - Pavčnik, Marijan (Podjetje in delo, 2014)
The primary content-related framework we are bound to are basic human rights as established in the Constitution. Basic rights may change and develop, yet as an heritage of our political and legal culture they possess such a solid core meaning that only "deliberate scepticism" (G. Radbruch) can doubt it. In societies with plural values, the moral values expressed by the basic human rights are the most solid moral basis of law. The moral understanding of law is necessarily accompanied by a moral critique of law. Such critique is often not pleasing to the authorities, but it cannot be avoided if one wants to bear responsibility towards nature, society and future generations. A lawyer who is not interested in these issues and only sticks to the letter of the law acts in a fossilized manner and does not enrich life that law is intended for. Legal thought should always have its sense, as Smole's Antigone would say.
Keywords: človekove pravice; human rights; law; morala; morality; pravni pozitivizem; pravo